The Gravettian of El Castillo revisited (Cantabria, Spain). (2nd March 2015) - Bernaldo de Quirós, Federico; Maíllo-Fernández, José-Manuel; Castaños, Pedro; Neira, Ana
Abstract: The long sequence of El Castillo cave contains Units 12 and 14, attributed to the Gravettian. This paper presents a revision of the lithic industry and the fauna recovered during H. Obermaier's 1910–1914 excavations of the site, as well as a number of new datings that enable us to chronologically place the above Gravettian occupations as one of the oldest in Europe. Unit 14 is dated between 34 and 33 ka cal BP and Unit 12 between 30 and 28 ka cal BP. The cave's oldest Gravettian level, Unit 14, presents techno-typological features typical of the first phases of the Gravettian in the Cantabro-Pyrenean region, such as Noailles burins, although it also shows some common elements with the Evolved Aurignacian. The youngest Gravettian unit, Unit 12, is characterised by laminar production from bipolar prismatic cores and a greater, albeit still discreet, presence of dorsal pieces. In terms of the fauna, Unit 14 is represented by red deer, chamois and horse, whereas Unit 12 is represented by red deer and horse, a hint as to what would later become the characteristic composition of Late Upper Palaeolithic faunal assemblages. The lithic and chronological characteristics of the Gravettian at El Castillo and the Cantabro-Pyrenean region lead us to believe in a mosaic formation of this techno-complex.